G185(P) Carnitine deficiency in long term parenteral nutrition (PN) dependent children. (24th May 2017) - Bhavsar, H; Forster, J
Abstract : Background: Serum Carnitine estimation is not part of routine monitoring on long term parenteral nutrition therapy. Carnitine deficiency (both primary and secondary) can present with inability to maintain blood glucose during the fasting state. This can be an important cause of hypoglycaemia in these patients during previously tolerated fasting periods. Case Report: Two year old with short bowel syndrome secondary to gastroschisis was admitted with mechanical break in the central line. He was exclusively dependent on PN for 16 hours a day and 7 nights a week. His enteral intake had been minimal due to various reasons in spite of measures to encourage oral and gastrostomy feeds. He developed symptomatic hypoglycaemia on the assessment unit while waiting for line repair not exceeding his usual fasting limit. His blood sugar was 0.8 mmol/L and this was treated appropriately. Hypoglycaemia screen done during this episode was normal except for low serum Carnitine of 3 umol/L (normal 15–53), suggesting diagnosis of Carnitine deficiency. Further paired serum Carnitine and urine Carnitine ruled out primary Carnitine deficiency with low serum Carnitine of 5 umol/L and free urinary Carnitine of 2 umol/L. His serum Lysine (precursor of Carnitine) level was also low at 75 umol/L (normal level 101–246). This was thought to be consistent with secondary (nutritional) Carnitine deficiency. He was started on enteral carnitine supplementation via gastrostomy with Carnitine level normalising (49 umol/L)within two weeks. Discussion and Conclusion: Carnitine plays a key role in the beta oxidation of fatty acids and its deficiency can lead to poor fasting tolerance. Endogenous Carnitine synthesis depends on its precursor lysine and is insufficient in children on minimal enteral nutrition. Most solutions for parenteral nutrition do not contain Carnitine. This makes PN dependent patients prone to develop nutritional Carnitine deficiency especially with minimal enteral feeding tolerance. Enteral supplementation of Carnitine normalised Carnitine level in our patient within two weeks and also improved fasting tolerance when prospectively monitored. He tolerated Carnitine supplementation well and is currently monitored for serum Carnitine levels regularly. We are currently screening our cohort of intestinal failure patients on PN for serum Carnitine levels and trying to co-relate this with their enteral intake. Low Caritine level in these patients may suggest routine screening for serum Carnitine in these patients to actively look for development of nutritional Carnitine deficiency.